CONTENTS (Medical Forum Monthly, 2024)
Presentation and Aetiological Aspects of Tuberculous Lymphadenitis at District Sialkot 2-4 Sajid Hussain 2. Anila Farooq 3. Ayaz AliCardiovascular and Renal Protection in Type 2 Diabetic Hypertensive Patients. The Role of Calcium Channel Blockers 5-8 Zeba Saeed 2. Syed Mohsin Turab 3. Munir Hussain Siddiqui 4. Afzal Qasim 5. Akhtar Ali Baloch 6. Jawad-us-Salam 7. Syeda Amber ZaidiEffects of Interferon Alpha on Thyroid Functions during Treatment of Chronic Hepatitis C 9-12Khadija MastoorFrequency and Causes of Conversion of Laparoscopic Cholecystectomy into Open Cholecystectomy 13-16 Shabab Hussain 2. Viqar Aslam 3. Muhammad Sherose Khan 4. Waheed Alam 5. Sajjad Muhammad Khan 6. Waqar Alam JanRole of Proton Pump Inhibitors in Chronic Cough 17-20 Mushtaque Ali Memon 2. Mukhtiar Hussain Jaffery 3. Muhammad ShafiTo Detect The Fungal Infection In Patients with Nasal Polyps 21-24 Muhammad Shafi 2. Mushtaque Ali Memon 3. Mukhtiar Hussain JafferyComparative study of Olopatadine hydrochloride 0.1% and Emedastine difumarate 0.05% comparing their Clinical Efficacy and Adverse Effects in Allergic Conjunctivitis 25-28 Bushra Sherwani 2. Muhammad Rashid Ahmed 3. Inayat ur Rahman 4. Muhammad ArifEruption time of Premolars in Children at Urban Schools of Lahore, Pakistan 29-32 Javed Iqbal 2. Riaz Ahmed Warraich 3. Rehan QamarStandard Interferon in the Treatment of Hepatitis C; Response Rate in Genotypes 2 and 3 from an Area in Azad Kashmir, Towards North of Pakistan 33-36 Waseem Ahmad 2. Muhammad Saleem 3. Fareeda Jamshed